Characteristics of adult education in european countries - Волярська, Олена Станіславівна; Пастушок, Ольга Іванівна (ScienceRise: Pedagogical Education, 2016)
In the article was considered a question of necessity of introduction of the system approach to organization of education of adult population in European space, to choice of optimal ways of the effective professional preparation of the different categories of adults for the diverse directions of qualification advance, determination of criteria of assessment of informal education of adults. There were grounded characteristics of professional training of specialists and unemployed people by the models on examples of Great Britain, Poland. There was determined the role of formal and informal education of adults. Formal education is given by the higher educational institutions – universities, institutions of postgraduate education, polytechnics and colleges. Informal education of adults is provided by the teaching associations, national educational institutions. There were determined the vectors of modernization of education of adult population: orientation on the real needs of customers (private persons and entrepreneurs); structural transparence and content flexibility of learning programs; multichannel financing; democratization of the system of education of adults by decentralization of managerial authorities. Conceptual principles of systematization of the prospects of development of education of adults in developed European countries are: determinism of educational policy of aforesaid countries by historical, political, national, socio-economic, cultural factors. We assign to the prospective directions of further researches: the theory and practice of education of adult population in the context of elaboration of civil society of the global scale; psychological adaptation of adults to the study and/or work in the foreign countries; acknowledge of the results of formal and informal education within international cooperation